Impacts of morally distressing experiences on the mental health of Canadian health care workers during the COVID-19 pandemic. Issue 1 (1st January 2021) - Plouffe, Rachel A.; Nazarov, Anthony; Forchuk, Callista A.; Gargala, Dominic; Deda, Erisa; Le, Tri; Bourret-Gheysen, Jesse; Jackson, Brittni; Soares, Vanessa; Hosseiny, Fardous; Smith, Patrick; Roth, Maya; et al.
ABSTRACT: Background: Research is urgently needed to understand health care workers' (HCWs') experiences of moral-ethical dilemmas encountered throughout the COVID-19 pandemic, and their associations with organizational perceptions and personal well-being. This research is important to prevent long-term moral and psychological distress and to ensure that workers can optimally provide health services. Objective: Evaluate associations between workplace experiences during COVID-19, moral distress, and the psychological well-being of Canadian HCWs. Method: A total of 1362 French- and English-speaking Canadian HCWs employed during the COVID-19 pandemic were recruited to participate in an online survey. Participants completed measures reflecting moral distress, perceptions of organizational response to the pandemic, burnout, and symptoms of psychological disorders, including depression, anxiety, and posttraumatic stress disorder (PTSD). Results: Structural equation modelling showed that when organizational predictors were considered together, resource adequacy, positive work life impact, and ethical work environment negatively predicted severity of moral distress, whereas COVID-19 risk perception positively predicted severity of moral distress. Moral distress also significantly and positively predicted symptoms of depression, anxiety, PTSD, and burnout. Conclusions: Our findings highlight an urgent need for HCW organizations to implement strategies designed to prevent long-term moral and psychological distress within the workplace. Ensuring availability of adequate resources, reducing HCW risk of contracting COVID-19, providing organizational support regarding individual priorities, and upholding ethical considerations are crucial to reducing severity of moral distress in HCWs. HIGHLIGHTS: We sought to evaluate associations between workplace experiences during COVID-19, moral distress, and the well-being of Canadian health care workers. Organizational variables predicted severity of moral distress. Moral distress predicted symptoms of mental health conditions.